A Review on Atomization and Sprays of Biofuels for IC Engine Applications. (June 2013) - Boggavarapu, Prasad; Ravikrishna, R. V.
Ever increasing energy requirements, environmental concerns and energy security needs are strongly influencing engine researchers to consider renewable biofuels as alternatives to fossil fuels. Spray process being important in IC engine combustion, existing literature on various biofuel sprays is reviewed and summarized. Both experimental and computational research findings are reviewed in a detailed manner for compression ignition (CI) engine sprays and briefly for spark ignition (SI) engine sprays. The physics of basic atomization process of sprays from various injectors is included to highlight the most recent research findings followed by discussion highlighting the effect of physico-chemical properties on spray atomization for both biofuels and fossil fuels. Biodiesel sprays are found to penetrate faster and have narrow spray plume angle and larger droplet sizes compared to diesel. Results of analytical and computational models are shown to be useful in shedding light on the actual process of atomization. However, further studies on understanding primary atomization and the effect of fuel properties on primary atomization are required. As far as secondary atomization is concerned, changes in regimes are observed to occur at higher air-jet velocities for biodiesel compared to those of diesel. Evaporating sprays revealed that the liquid length is longer for biodiesel. Pure plant oil sprays with potential use in CI engines may require alternative injector technology due to slower breakup as compared to diesel. Application of ethanol to gasoline engines may be feasible without any modifications to port fuel injection (PFI) engines. More studies are required on the application of alternative fuels to high pressure sprays used in Gasoline Direct Injection (GDI) engines.